The Influence of Corporate Governance on The Financial Performance of The Asian Stock Market of Large Companies - Yaseen, Maytham Taha; Hasan, Esraa Mohammed; Jasim, Sawsan Fadhil; Kadhim, Salam Radhi; Sabti, Yousif Mousa (South Asian Journal of Social Sciences and Humanities, 2024)
The research aimed to know the impact of corporate governance with its variables (board size and board independence) on the financial performance of large Asian companies in the stock market. To achieve the research objectives, the study used the analytical approach and collected data from the stock market from 2019 to 2023 for 118 large company. Financial performance was also evaluated by using the rate of return on assets. The results concluded that there is a positive and important relationship between corporate governance with its variables (board size and board independence) with financial performance. The study indicates increased awareness and interest by the management of public shareholding companies regarding the importance of adhering to the rules of governance.